2016
DOI: 10.1016/j.athoracsur.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Clinical Outcome of Endoscopic Versus Open Radial Artery Harvesting: A Propensity Score Analysis

Abstract: Endoscopic radial artery harvesting allows for incremental benefits in the short term in terms of improved cosmesis and reduced wound and neurologic complications, without yielding detrimental effects in terms of graft-related events at 5 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Same result was reported in previously cited study, where 98% of pts were satisfied, and only 1.6% considered scar as extremely bad [9]. Very good cosmetic results were also reported by others, after using endoscopic technique [2,15,16].…”
Section: Esthetic Satisfaction and Arm Painsupporting
confidence: 84%
“…Same result was reported in previously cited study, where 98% of pts were satisfied, and only 1.6% considered scar as extremely bad [9]. Very good cosmetic results were also reported by others, after using endoscopic technique [2,15,16].…”
Section: Esthetic Satisfaction and Arm Painsupporting
confidence: 84%
“…Search result and study characteristics. Overall, 9 RCTs [24][25][26][27][28][29][30][31][32], 3 NRCTs with propensity score matching [33][34][35], and 12 NRCTs [36][37][38][39][40][41][42][43][44][45][46][47] were included. All studies included were published in English.…”
Section: Search Resultsmentioning
confidence: 99%
“…In a PSM study by Navia et al no difference was found between the two techniques in terms of wound infection and neurological deficits. However, Bisleri and coauthors found that open RA harvesting was associated with increased wound infection (7.3% vs 0.0%; p = 0.007), poorer wound healing using the Hollander scale (3.3 vs 4.7, p < 0.001), and increased prevalence of paresthesia at long term follow‐up (19.5% vs 3.6%; p < 0.001) …”
Section: Discussionmentioning
confidence: 99%